MODERATE ISLAM AND ITS RELEVANCE IN THE POST 9/11 AMERICA AS IMPLIED IN IMAM FEISAL ABDUL RAUF’S MOVING - Rifka Pratama (Universitas Gadjah Mada, 2016)
American Muslim is one of some existing religious minorities in America. Despite of minority, this religious group has been long, some believed it has been even since the Columbus exploration, living in the country. As time goes, the American Muslims are able to blend with American Society. These Muslim individuals are found in many fields of life of American, such as social, economic, education, and even politics in America. This condition is anyway worth appreciating as the struggle of American Muslims for their existence is not something simple and easy. Apart from the reality, the deadly attacks of 9/11, to some extent, has put American Muslims to be objects of suspicions. Soon after the tragedy, Muslims in many occasions are prejudiced as harsh, and of course, terrorists. These suspicions and prejudice have been, in fact, long found in the middle of American society pre-9/11 attacks. However, the tragedy aggravates the status quo of the American Muslims and it soon creates the worst point of so-called Islamophobia. In response to this phenomenon, many American Muslims start to deliver counters in various ways and media. Among the American Muslim figures, Imam Feisal Abdul Rauf, an American Muslim activist and leader, actively brushes off the bad images of Islam, especially regarding the 9/11 tragedy. Through his book entitled “Moving the Mountain: beyond Ground Zero to a New Vision of Islam in America”, Rauf explains his views on Islam. This book also implies counters to the so-called phenomena of Islamophobia. On the other hand, Moderate Islam contains the same spirits with Rauf’s Moving the Mountain. It offers the spirit of moderation in understanding and practicing Islam. Both the ideas in turn are able to counter Islamophobia in America, especially in post 9/11 America.Keyword: American Muslims, Imam Feisal Abdul Rauf, Moving the Mountain,Islamophobia, Moderate Islam